KEPUTUSAN GATEKEEPER DALAM MENENTUKAN LAYAK TIDAKNYA SEBUAH BERITA: Rubrik Metro Palu Di Harian Metrosulawesi Palu - Saputra, Tri Ramanandha; Akifah, Andi; Wahid, Muhammad (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2019)
This study aims to find out what criteria are set by the gatekeeper at the Metrosulawesi Daily in determining whether or not a news item is worthy of publication and to find out what methods are used by gatekeepers at the Metrosulawesi Daily in resolving news writing errors. This study uses participant observation with a qualitative descriptive research approach as well as using a qualitative content analysis research method that uses a variant approach to the qualitative case study methodology which. The results of this study found that the gatekeeper of the Metrosulawesi daily in determining whether or not a news item was appropriate prioritized the economic aspect as the main guideline in gatekeeping. While the other 6 aspects as mentioned by Bittner only have a small influence on the gatekeeper in determining whether or not a news is worthy. Based on the research obtained, it can be concluded that the gatekeeping process carried out in the Metro Palu rubric is more inclined to the aspect of economic needs. For gatekeepers in determining whether or not a news is appropriate, the economic aspect is a basic guideline for companies to survive in the middle of media competition in Palu City. The economic aspect in the gatekeeping process in the Metrosulawesi daily can even shift the role of the gatekeeper in selecting every information. This is because the presence of advertisements, sponsors and advetorials is the main source of life for the survival of the Metrosulawesi Daily. In resolving writing or reporting errors, the Metrosulawesi daily chose to meet directly with sources to confirm the reporting errors. Then repackaging the false news, then republish it so that misunderstandings can be resolved without legal action.